Development of Augmented Reality Learning Media to Introduce Musical Instruments for Deaf Elementary School Student - Saputri, Dian Syafitri Chani; Anggrawan, Anthony; Susilowati, Dyah; Maulana, Rahmat (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop Augmented Reality learning media for deaf children at the elementary school level in recognizing musical instruments and measuring their effectiveness on learning outcomes. The research method used is research and development (R&D) and uses the Multimedia Development Life Cycle development method. The effectiveness of the media was tested using pretest-posttest. Data analysis techniques use the parametric statistical test. The results of testing by media and content experts concluded that the application was declared suitable for use as a learning medium. From the beta test, it was discovered by 33 deaf students that Augmented Reality learning media was well received. The t-test comparison test shows that there is a difference, which means that the use of Augmented Reality learning media as a medium for introducing musical instruments to deaf students has a positive impact on learning outcomes.